Gender aspects of irrigation management: The Chhattis Mauja Irrigation System in Nepal - Zwarteveen, M.Z.; Neupane, N. (1995)
Although irrigated farming in the head end of the Chhattis Mauja irrigation system in Nepal is increasingly the responsibility of women, female farmers do not formally participate in the schemes' organization. However, women's non-involvement as formal members in meetings, and the lack of female representation in the organization does not seem to negatively affect their access to irrigation services. On the contrary, women succeed extremely well in getting their irrigation needs accommodated. This is due partly to the very fact that they are not formally participating in the scheme's management; this allows them to take more water than they are entitled to and to contribute less labor to maintenance than they should without being punished. Because women are not recognized as members, the organization faces difficulties in enforcing its rules on women. At the same time, female farmers cunningly make use of the prevailing gender ideology which pictures them as weak and in need of protection. This ideology, although it does not reflect realities as perceived by women themselves, does strengthen them in their negotiations for more water and in their attempts to minimize their contributions to the schemes' maintenance.